Current status of discrete data capture in synoptic surgical pathology and cancer reporting - Williams CL; Bjugn R; Hassell LA (Dove Medical Press, 2015)
Christopher L Williams,1 Roger Bjugn,2 Lewis A Hassell1 1Department of Pathology, University of Oklahoma Health Sciences Center, Oklahoma City, OK, USA; 2Department of Pathology, Oslo University Hospital, Oslo, Norway Abstract: The current status of synoptic pathology reporting is presented with its historical context. The awareness of additional audiences and users has made the presentation and capture of pathology data, particularly cancer data of broad importance. Current models of adoption in the US, Canada, Norway, and the Netherlands are noted. Significant terms, benefits, and stakeholders key to implementation and advancement of capabilities particularly with regard to capture of discrete data elements are presented. Important barriers to be overcome include fiscal constraints, technologic barriers such as interconnectivity and legacy systems, as well as social and organizational obstacles. Keywords: quality assurance, integrated disease reporting, clarity, completeness, pathology report, cancer registry, biorepository